Analysis of Morphological Characteristics of Male and Female Gymnocypris eckloni Herzenstein - Qiming Wang; Suxing Fu; Xiaoyi Chen; Yuting Duan; Luo Lei; Yawen Fan; Chaowei Zhou (Fishes, 2025)
Accurate sex identification is crucial for the artificial breeding of fish species, and identification based on phenotypic traits is the preferred method owing to its low cost and rapidity. This study aimed to investigate morphological differences between male and female Gymnocypris eckloni Herzenstein. A total of 166 G. eckloni individuals (83 males and 83 females) were included, and 20 morphological indicators, including head length, snout length, and body weight, were measured. Various analytical methods, such as correlation analysis, principal component analysis, discriminant analysis, and systematic cluster analysis, were used to compare the morphological characteristics of male and female G. eckloni. The result showed significant differences in morphological characteristics between male and female individuals (p ≤ 0.05). Principal component analysis revealed five main components that collectively contributed to 83.64% of the variance, primarily including body length, fork length, total length, and body weight, highlighting the significance of these components in sex differentiation. Subsequently, a mathematical model was constructed via discriminant analysis. This model demonstrated an accuracy of 79.5% and 73.5% in identifying male and female G. eckloni, respectively, with an overall accuracy of 76.50%. Furthermore, on analyzing the relationship between body length and body weight in G. eckloni, we found differences in growth patterns between sexes. In particular, female fish usually weighed more than male fish, which was consistent with the biological characteristics and energy distribution patterns of G. eckloni. These results suggest that sexual dimorphism in G. eckloni is primarily concentrated in body shape and head morphology, which provides a reliable basis for sex identification based on morphological differences.